Prática pedagógica e necessidades educacionais especiais: a relação diádica em sala de aula - Garcia, Valéria Paiva Casasanta (2005)
Considering the school educational process of mental deficient student, the research purpose was comprise the pedagogical practice aspects of their teachers. For it, we analysed the pedagogical practices of two teachers that work for the First Series of Basic Teaching, considering that one of them work at a regular municipal school and the other at a special school. This study entered on a brief theoretical review about the Brazilian Special Education History and the evolution of the school attending sorts offered to the mental deficient people. To comprise the acquired data we used how theoretical review the Social-Historical Theory by Lev Semenovich Vygotsky and the ecological approach of the Human Development by Urie Bronfenbrenner. Inside the social-historical approach we can emphasize the intervention concept in the comprehension of educational act and the importance of social relations to structure the human conscience along the formal educational process. We used the ecological approach by Urie Bronfenbrenner to consider that a school is a social space able to suffer direct and indirect influences from other systems, displaying in the teacher/student duet the interaction impact lived for the both. We delimited the methodological option to a qualitative approach developed in parameters of the ethnographic case study. How strategy to examine and acquire the data was used the Reflexive Interview from the observation register that, in the research environment, provided to participant teachers a reflection space about their pedagogical practice, providing meaningful changes in their way to discern and to explain the events regarding to these practices and, consequently, challenging changes in their pedagogical actions inside the classroom micro system. The acquired data showed that the pedagogical practice of the mental deficient student teachers must be comprise considering some factors that appear permanently acting on it; for example: the teachers doubts face to the complexity of educational act to teach for mental deficient students; the absence of specific qualification for this teachers in the special education area; the conceptions of development and mental deficiency that aid the teaching practice; the predominance of divergent values between family and school.; and, the dichotomy between the studied theory by teacher and its practical actions in the classroom. On that score, we verify that the educational practices established by teachers of mental deficient children were based on activities that little explored the students abstract thinking, emphasizing the unstructured, repetitive and little meaningful tasks considering the specific features of each student whereas creatures historically established, inside an interaction and specific cultural context.